Enhancing Cognitive Development And Creativity Through â€œTikasanâ€ Loose Parts Media - Warning, Warning; Muhajir, Muhajir (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aims of this study was to determine whether the â€œTIKASANâ€ Loose Parts media can enhance cognitive development and creativity in Group B. The research employed a quantitative approach with experimental methods, utilizing a quasi-experimental design with a singular treatment model. The study population comprised children aged 5-6 years in Group B at Putra Bangsa Kindergarten. The experimental group included 15 children in Class B1 and 15 children in Class B2. This research differs from prior studies by incorporating a unique medium, â€œTIKASAN.â€ Â Research data collection involved observation, documentation, and research instruments. Statistical analysis utilized parametric homogeneity tests. The results indicate that: 1) â€œTIKASANâ€ Loose Parts media significantly influences cognitive development in Group B; 2) â€œTIKASANâ€ Loose Parts media positively impacts creativity development in Group B; 3) Overall, â€œTIKASANâ€ Loose Parts media has an influence on both cognitive development and creativity in Group B.